2008
DOI: 10.1007/s10666-008-9174-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Groundwater Level Estimation Using Neuro-fuzzy and Ordinary Kriging

Abstract: Water level in aquifer plays the main role in groundwater modeling as one of the input data. In practice, due to aspects of time and cost, data monitoring of water levels is conducted at a limited number of sites, and interpolation technique such as kriging is widely used for estimation of this variable in unsampled sites. In this study, the efficiency of the ordinary kriging (OK) and adaptive network-based fuzzy inference system (ANFIS) was investigated in interpolation of groundwater level in an unconfined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The ANFIS model overcomes the more traditional methods of electrical conductivity modelling based on the total dissolved solids in water. In 2009, Kholghi and Hosseini (2009) applied the neuro-fuzzy model and the kriging method for the water level assessment, in the Qazvin plain (Iran), in areas where no data were available. The neurofuzzy models manage the uncertainty and lack of data well.…”
Section: Introductionmentioning
confidence: 99%
“…The ANFIS model overcomes the more traditional methods of electrical conductivity modelling based on the total dissolved solids in water. In 2009, Kholghi and Hosseini (2009) applied the neuro-fuzzy model and the kriging method for the water level assessment, in the Qazvin plain (Iran), in areas where no data were available. The neurofuzzy models manage the uncertainty and lack of data well.…”
Section: Introductionmentioning
confidence: 99%
“…[19]. Ordinary kriging is a linear weighted-average technique which is unbiased with regard to the expected value of residuals [22]. In this context, we assume that the mean is constant in the local neighborhood of each estimation point and m(u) = m(u α ) for each nearby data value and Z(u α ) is used to estimate Z(u) [23].…”
Section: Coastline Extractionmentioning
confidence: 99%
“…Kriging has been broadly used in geology, hydrology, environmental monitoring, atmospheric sciences and pedology for interpolation of spatial data (McBratney et al, 1982;Stein, 1999;poon et al, 2000;Gringarten and deutsch, 2001;Jost and et al, 2005;Kholghi and hosseini, 2009;Oliver and webster, 2014;Jeihouni et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They showed that ANFIS with a few data has better capability to model EC than regression based conventional methods. Kholghi and hosseini (2009) compared both ANFIS and OK to estimate groundwater level and they found that ANFIS is more efficient than OK. Kazemi and hosseini (2011) studied OK, ANN and ANFIS for interpolating heavy metals in the Caspian Sea and they reported that ANFIS is the model with the lowest simulation error.…”
Section: Introductionmentioning
confidence: 99%